Chemical composition of organically and conventionally grown fruits of raspberry (Rubus idaeus L.) cv. Willamette - Milinković Mira (University of Kragujevac, Faculty of Agronomy, Cacak, 2021)
The paper presents two-year results of chemical tests of raspberry fruits in organic and conventional cultivation systems. Raspberry plantations were established on the slopes of Jelica Mountain, on soil having very acidic reaction (pH/KCl 3.67-3.76) and optimal contents of humus and total N. In the conventional cultivation system, the soil had a high supply of readily available P2O5 and K2O and microelements, with excessive levels of Ni, and Cr. In the organic system, the content of Ni and Zn increased. The biochemical properties of organic and conventional fruits showed no significant differences, while the influence of the research year and the interaction of the cultivation system showed significant differences in the content of TA and IS. However, higher values of the levels of soluble solids, total acids and sugars contributed to the more appealing taste and aroma of organic raspberry fruits. The contents of microelements and heavy metals in the fruits of both cultivation systems were measured in the following order Mn>Fe>Zn>Cu>Ni>Cr>Co. No significant difference was found in the contents of the examined elements between organic and conventional fruits, except for the statistically higher content of Fe in organic raspberries. The high share of individual elements (especially Ni) in both cultivation systems indicates the need for continuous chemical testing of soil and fruits. Based on the results, it is important to consider the daily intake of each element in relation to body weight and/or maximum daily intake.